Relationship among air void microstructural characteristics, stiffness, and fatigue of asphalt concrete mixtures - de Souza, Thiago Delgado; Enríquez-León, Alexis Jair; Hennig Osmari, Patrícia; de Barros, Larissa Montagner; de Oliveira, Alex Duarte; Aragão, Francisco Thiago Sacramento; Pereira, André Maués Brabo (Road materials and pavement design, 2023)
It is a common sense that the air void content significantly affects the field performance of asphalt mixtures. Thus, this parameter is a key mix design criterion and is also adopted as a quality assurance/control tool. Even though the air voids play a notorious role in the behaviour of asphalt mixtures, the knowledge about their microstructural characteristics is still limited. To overcome this limitation, advanced techniques such as the X-ray micro-computed tomography technology may be pursued as an alternative. This paper uses X-ray micro-computed tomography to identify microstructural parameters of air voids within asphalt mixtures, i.e. distribution, content, type, size, and degree of anisotropy. These microstructural characteristics are compared to the stiffness and the resistance to fatigue cracking of asphalt mixtures. The findings suggest that the air void distribution is strongly correlated with the mixture stiffness and fatigue behaviour, and that the air void heterogeneity should be avoided.